Association of Raised Troponin Levels With Mortality in Acute Ischemic Stroke Patients - Jamil, Maryam; Shabbir, Bilquis; Arif, Zia; Nadeem, Maria (Biological and Clinical Sciences Research Journal, 2025)
Troponin-T is a well-established cardiac biomarker used primarily in diagnosing myocardial infarction. However, its elevation in acute ischemic stroke (AIS) patients has been increasingly recognized as an indicator of poor prognosis. Elevated troponin-T levels may result from direct neurogenic myocardial injury or underlying cardiac pathology and may serve as a useful prognostic marker for mortality in stroke patients. Objective: To determine the association of raised troponin-T levels with short-term mortality in patients presenting with acute ischemic stroke. Methods: This prospective observational study was conducted at the Department of Medicine, Sir Ganga Ram Hospital, Lahore, from June 15, 2024, to December 14, 2024. A total of 200 patients with confirmed acute ischemic stroke were enrolled. Serum troponin-T levels were measured using centrifuged serum samples. Patients were categorized into two groups: Group A (raised troponin-T levels) and Group B (normal troponin-T levels). All patients were followed up for a period of 3 months to record mortality. Data were analyzed using SPSS v25. Mortality risk was compared between groups using Chi-square test, with relative risk (RR) and 95% confidence interval (CI) calculated. A p-value < 0.05 was considered statistically significant. Results: Among 200 patients, 67.5% (n = 135) were male and 32.5% (n = 65) were female. The mean age was 49.83 ± 7.79 years. Hypertension and diabetes were present in 49.0% and 37.0% of patients, respectively. Obesity was seen in 20.5% (mean BMI = 24.32 ± 1.87 kg/m²), and 34.0% were smokers. Overall mortality was 13.0% (n = 26). Group A (raised troponin-T) showed a significantly higher mortality rate of 20.0% (n = 20) compared to 6.0% (n = 6) in Group B (p = 0.003). The relative risk of mortality in Group A was 3.97 (95% CI: 1.50–10.22), indicating a strong association. Conclusion: Raised troponin-T levels are significantly associated with increased mortality in acute ischemic stroke patients. Routine assessment of troponin-T in such patients can aid in early risk stratification and guide intensive monitoring and management. Early identification of high-risk patients could reduce mortality and improve overall outcomes.